Hepatoprotective Effects of Crude Stem Bark Extracts and Solvent Fractions of Cordia africana against Acetaminophen-Induced Liver Injury in Rats - Gudeta Duga Geresu; Shemsu Umer; Mahlet Arayaselassie; Genet Ashebir; Eyasu Makonnen (Canadian Journal of Gastroenterology and Hepatology)
Cordia africana Lam (Boraginaceae) is widely used in Ethiopian folk medicine for the treatment of different types of liver disorders. Thus, this study aimed to investigate the hepatoprotective effects of an aqueous (CAAE), 80% methanol extracts of C. africana stem bark (CAME), and the solvent fractions of the methanol extract against acetaminophen (APAP)-induced liver injury in rats. Acute toxicity test and APAP-induced lethality test were done on mice of either sex, while APAP dose selection test was done on female rats. Male rats were used for hepatoprotective experiments and the liver injury was induced using 2 g/kg APAP given orally. Serum levels of the liver enzymes and total bilirubin (TB), as well as lipid profiles, were determined. Histopathological examination of the liver tissues was also conducted to confirm the findings of biochemical analysis. Intraperitoneal (i.p.) sodium pentobarbital (SPB)-induced sleeping duration was also used to determine the protective effect of the test substances. Oral administration of APAP resulted in a significant increase in serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), TB, low-density lipoprotein (LDL), total cholesterol (TC), and triglycerides (TGs) and decrease in serum high-density lipoprotein (HDL). Administration of the standard drug, silymarin 100 mg/kg, extracts at doses of 100, 200, and 400 mg/kg and fractions at the dose of 400 mg/kg reversed the serum levels of all parameters to normal. CAME exerted a significant dose-dependent hepatoprotective effect in terms of ALT and AST, while CAAE significant dose-dependent hepatoprotective effect was in terms of AST, ALP, and TGs. The protective effect of the extracts and fractions was also confirmed by histopathological investigations and SPB-induced sleeping time. From the results of the present study, it can be concluded that C. africana stem bark aqueous, 80% methanol crude extracts, and solvent fractions of the methanol extract showed hepatoprotective effects.